2020
DOI: 10.3390/vetsci7030108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Unconventional Supplements to the Diet of Intensively Reared Agouti (Dasyprocta leporina) in Trinidad, West Indies

Abstract: A feed trial was carried out to evaluate potential unconventional feed resources such as Trichanthera gigantica and moruga hill rice (Oryza glaberrima) as a partial supplementation to the diet of adult male agoutis (Dasyprocta leporina). Supplemental feeding of the agouti will decrease feeding cost to produce this animal and aid in sustainable agricultural practices. Male agoutis were used as this physiological state was the easiest to attain as well as male animals are generally used for meat production. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In the management of the agouti, the specific nutritional requirements for the agouti are unknown. John and Jones [ 11 ] showed that agouti can maintain their adult bodyweight on a 17% crude protein diet. However, the protein requirement for growing (juvenile) animals is currently unknown, and the locally available fruits and rabbit ration supplementation may not have adequate nutrients for this physiological state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the management of the agouti, the specific nutritional requirements for the agouti are unknown. John and Jones [ 11 ] showed that agouti can maintain their adult bodyweight on a 17% crude protein diet. However, the protein requirement for growing (juvenile) animals is currently unknown, and the locally available fruits and rabbit ration supplementation may not have adequate nutrients for this physiological state.…”
Section: Discussionmentioning
confidence: 99%
“…e agouti is a medium-sized rodent (2-3 kg) that produces two offsprings per parturition [6] with a gestation period of 103 days [7]. ese animals have an omnivorous diet [8][9][10][11] and are able to consume agricultural by-product [12]. Young animals can be weaned at one month and can reach market weight at nine months [13].…”
Section: Introductionmentioning
confidence: 99%
“…These animals are ideal for sustainable agriculture as they have the ability to utilize locally available feedstuff and convert them into animal protein. They can be fed locally available forages and feed by-products for maintenance [ 3 ]. The agouti ( D.leporina ) is considered by some authors as an opportunistic feeder [ 4 ], others have considered these animals as omnivores as they can consume both plant and animal matter [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%